Women and risk-taking behaviour in local public finance. Issue 12 (2nd December 2018) - Suzuki, Kohei; Avellaneda, Claudia N.
ABSTRACT: This study examines how female representation in local elected (mayor and legislature) and administrative (mid-level manager) positions influences municipal financial decision-making in 764 Japanese city-level governments. Findings show that female representation in local councils is positively correlated with risk-averse behaviour in financial decisions, as female representation on the legislature is negatively associated with issuing municipal bonds and with local investment in public corporations. Female representation in executive (mayor and vice-mayor) and mid-level administrative managerial positions has no apparent effects on local financial decisions. This study tests existing explanations of relationships between female managerial representation and fiscal behaviour in an Asian developed setting characterized by considerable underrepresentation of women in politics.